Les lieux de vie collectifs et écologiques, acteurs du renouveau endogène des territoires ruraux de basse densité en France et au Québec : un enjeu de gouvernance territoriale - Florent Amat (L'Espace Politique)
Since the late 1990s, Western rural areas are witnessing an increasing phenomenon of a particular type of urban to rural migrations led by social and ecological considerations. This contributes to the eruption of alternative lifestyles opposed to the mainstream urban way of life, taking part in what Halfacree calls the radical rural. Supported either by newcomers or long-time residents in rural spaces, those alternatives are built on place-based experimentation and exemplariness. This distinguishes them from militant or partisan projects. Some projects take place within low-density rural areas and contribute to their revival from within, while sparking off debates between conventional, traditional and alternative socio-spatial representations of rural spaces. Doing so, they get involved in and challenge local governance. We are interested in a specific category of rural alternatives: ecological community living. Those are micro-political initiatives led by at least three people, beyond the nuclear family, with the purpose of living according to their beliefs. They particularly aim at promoting ecology and solidarity at least within their own community. However, most of them are also aiming at a broader diffusion of their ideas and practices. We show how some projects which aim at putting down roots locally can impact local dynamics, contrary to others being more oriented towards trans-local networks. Our research is based on qualitative data issued from a multiple case study in Gaspésie (Quebec, Canada), Ariège and Orne (France). More precisely, we draw on 66 cumulative days of participant observation within 14 ecological communities, 33 semi-directive interviews with rural actors –either community members or public actors–, as well as informal interviews and document analysis. Our research is in line with the works on the construction of rural and rurality in a context of restructuration of rural spaces. It also draws on the French-speaking research on everyday life alternatives. Within these approaches, we apply Jodelet’s definition of representation to the French theoretical approach of local governance (gouvernance territoriale). We first introduce how various projects show uneven bonds with rural communities, and how they are confronted to polarizing socio-spatial representations. Then, we explore three cases to show the extent to which collectives' relationship with the communities is determined by a combination of endogenous, exogenous and contextual factors. Eventually, we examine local elected representative and public servant’s ambivalent perspective upon ecological community living, which can be perceived as opportunities as much as threats regarding their own local governance mission. In conclusion, rural alternatives act both as local actors and as representatives of supra-local interests working for broader social change. Hence, this article contributes both to the literature on the radical rural and on local governance in rural spaces, in a context of increasing multifunctionality and climate crisis.